Three Brachypodium distachyon Uev1s Promote Ubc13-mediated Lys63-linked Polyubiquitination and Confer Different Functions - Guo, Huiping; Wen, Rui; Wang, Qianqian; Datla, Raju; Xiao, Wei (Frontiers in Plant Science, 2016)
In this study, we report the identification and functional characterization of three Brachypodium distachyon UEV genes. All three BdUev1s form heterodimers with BdUbc13s, which are capable of catalyzing Lys63-linked polyubiquitination in vitro. The three BdUEV1 genes are also able to functionally complement the budding yeast mms2 mutant defective in DNA-damage tolerance. BdUev1A differs from the other two BdUev1s in that it contains an 18-amino acid tail, which appears to compromise its function in yeast, as deletion of this tail restores full function. BdUev1A is located in the cytoplasm and plasma membrane but not in the nucleus, whereas BdUev1B, BdUev1C and the C-terminally-truncated BdUev1A are mainly found in the nucleus. These and the BdUEV1 gene expression analysis allow us to speculate that although all three BdUev1s function by promoting Lys63-linked polyubiquitination, BdUev1B and BdUev1C are involved in DNA-damage response and possibly other nuclear functions, while BdUev1A is required for non-nuclear function(s).